GaN Micropillar Schottky Diodes with High Breakdown Voltage Fabricated by Selective‐Area Growth. Issue 7 (21st October 2019) - Debald, Arne; Kotzea, Simon; Riedel, Jona; Heuken, Michael; Kalisch, Holger; Vescan, Andrei
Abstract : Herein, selective‐area growth (SAG) of lightly n‐doped GaN micropillars on masked GaN‐on‐sapphire templates is investigated. Using the micropillar SAG approach, the maximum GaN drift layer thickness in Schottky diodes on foreign substrates is increased. Thus, cost‐efficient vertical power devices with large breakdown voltages ( V BD ) based on heteroepitaxy are enabled. The influence of different hard‐mask materials and SAG temperatures ( T SAG ) on growth selectivity, morphology, and net doping concentration ( N D – N A ) is investigated. By using an AlOx hard mask and T SAG  = 1045 °C, 3.7 μm high GaN micropillars are grown in circular mask openings. Quasi‐vertical Schottky diodes on these pillars exhibit low N D – N A  = 5.2 × 10 16  cm −3, V BD  = 393 V, and a critical electric field E C  = 2.63 MV cm −1 . Abstract : Herein, GaN micropillars are fabricated utilizing metal organic vapor phase epitaxy (MOVPE) selective‐area regrowth. Following this approach, limitations of the maximum thickness of the epitaxial stack and thus the achievable breakdown voltage are circumvented. GaN micropillar Schottky diodes with moderate drift layer thickness and excellent electrical characteristics are realized, and the proof of concept for thick drift layers is demonstrated.